2016
DOI: 10.1016/j.ygeno.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

HyCCAPP as a tool to characterize promoter DNA-protein interactions in Saccharomyces cerevisiae

Abstract: Currently available methods for interrogating DNA-protein interactions at individual genomic loci have significant limitations, and make it difficult to work with unmodified cells or examine single-copy regions without specific antibodies. In this study, we describe a physiological application of the Hybridization Capture of Chromatin-Associated Proteins for Proteomics (HyCCAPP) methodology we have developed. Both novel and known locus-specific DNA-protein interactions were identified at the ENO2 and GAL1 prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Important progress has been made for multi-copy DNA loci such as repetitive DNA elements [7][8] . Recently, oligo-capture 44 and CRISPR-Cas9 technology 45 have been applied to identify proteins at single copy genomic loci. However, the problem of assessing a unique locus in a comprehensive and quantitative manner by mass spectrometry has not been solved and many challenges remain, a major one being the high degree of purification of the locus of interest while obtaining sufficient material for good coverage in MS analysis 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Important progress has been made for multi-copy DNA loci such as repetitive DNA elements [7][8] . Recently, oligo-capture 44 and CRISPR-Cas9 technology 45 have been applied to identify proteins at single copy genomic loci. However, the problem of assessing a unique locus in a comprehensive and quantitative manner by mass spectrometry has not been solved and many challenges remain, a major one being the high degree of purification of the locus of interest while obtaining sufficient material for good coverage in MS analysis 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Novel findings on Pab1 functions are continuously emerging, indicating that the role of this protein in cell physiology could be larger than expected. For example, chromatin immunoprecipitation assays revealed that Pab1 binds DNA at the ENO2 and GAL1 promoter and that the carbon source can alter Pab1 enrichment at the promoter site (Guillen‐Ahlers et al, ). This result suggests a possible role of Pab1 in the regulation of transcription and/or in the epigenetic control of chromatin function (Byrum, Raman, Taverna, & Tackett, ; Guillen‐Ahlers et al, ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…We have used an approach known as HyCCAPP, or hybridization capture of chromatin-associated proteins for proteomics. 23,24 Briefly, human K562 cells are cross-linked using formaldehyde to fix protein-DNA interactions, then cells are lysed and chromatin is sheared. The lysate is incubated with biotinylated capture oligonucleotides, whose sequences are designed to complement the human alpha satellite consensus sequence, 25 and hybridized complexes are isolated using streptavidin-coated magnetic beads.…”
Section: Introductionmentioning
confidence: 99%
“…HyCCAPP has proven to be a useful tool, revealing both known as well as novel protein-DNA interactions in yeast. 23,24 Here, we apply HyCCAPP to the human genome for the first time, providing a DNA-centric lens through which to view protein-alphoid DNA interactions. Using this approach, 90 proteins were identified as enriched at the alpha satellite repeats, including many known centromere-binding proteins in addition to a number of novel alpha satellite-binding proteins, which may provide new insights into centromere structure or function.…”
Section: Introductionmentioning
confidence: 99%